Clinical features and enzyme replacement therapy in 10 children with Fabry disease - Li, Qian; Wang, Jing; Tian, Minle; Yang, Zhenle; Yu, Lichun; Liu, Suwen; Wang, Cong; Wang, Xiaoyuan; Sun, Shuzhen (Frontiers in Pediatrics, 2023)
Objective To summarize the clinical features and enzyme replacement therapy(ERT) of Fabry disease (FD) in children. Methods The clinical data, laboratory tests, genetic variations and treatment of 10 FD children diagnosed in Shandong Provincial Hospital from September 2020 to June 2022 were retrospectively analyzed. Results Among the 10 cases from 6 families, 7 patients were boys of 4 to 13 years of age, and 3 were girls of 12 to 15 years of age. There were 7 symptomatic patients, including 6 boys and 1 girl. All 7 patients presented with acral neuralgia. Five patients had little or no sweating. Five patients presented with cutaneous angiokeratoma. Two patients had abdominal pain. One patient developed joint symptoms. Four patients had corneal opacity. One patient had hearing loss; one patient had short stature. One patient had mild proteinuria and 1 patient had dysplasia of the right kidney with decreased eGFR (55.28 ml/min.1.73 m2). The left ventricular mass index was slightly elevated in 1 patient. Three patients had mild obstructive ventilatory dysfunction; a small amount of effusion in the intestinal space of the lower abdomen or mild fatty liver was found in 2 patients. Partial empty sella turcica in 1 patient. A total of 6 GLA gene variants were detected in 10 children, among which C.1059_1061delGAT (p.met353del) was a newly discovered mutation. Five children received ERT, of which 4 were treated with agalsidase beta and 1 was treated with agalsidase alpha. Only 1 patient had anaphylaxis. Lyso-GL-3 levels decreased significantly in the first 3 months of ERT initiation and remained relatively stable thereafter in 3 patients. The Lyso-GL-3 level was decreased, but renal impairment continued to progress in 1 patient treated with agalsidase alpha. Conclusion The clinical manifestations of FD in childhood are diverse, and it is necessary to make a definite diagnosis by combining family history, enzyme activity, biomarkers, gene testing and other indicators. Pedigree screening and high-risk population screening are helpful for early identification, early diagnosis and early treatment. No serious adverse reactions were found during the short-term treatment with agalsidase alpha and beta.